PENGARUH RISIKO LIKUIDITAS DAN RISIKO KREDIT TERHADAP PROFITABILITAS - Algiansah prayogi; R, Deni Muhammad Danial; Dicky Jhoansayah (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2024)
The purpose of study is to determine the effect of Liquidity Risk on Profitability and find out Credit Risk on Profitability in state-owned bank companies listed on the Indonesia Stock Exchange for the 2013-2020 period. The effect in this study are Liquidity Risk (X1), Credit Risk (X2) and Profitability (Y). The Research method used is the descriptive and assosiative analysis with a quantitative approach. the samples used were 4 out of 58 samples using a purposive sampling technique. The data analysis, testing the research model (F test) and testing the hypotesis using (T test) with data processing using SPSS 21 soft ware. Based on the results of the study, it shows that there is an influence of the variable Liquidity Risk (X1) and Credit Risk (X2) on Profitability (Y) of 1.111 including the recognition of a strong relationship, (1) Liquidity Risk has a negative and not significant effect on Profitability of 0,380 or 3,80% , (2) Credit Risk has a negative and significant effect on Profitability of 0,731 or 7,31%.